2023
DOI: 10.1186/s41077-023-00244-5
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of repeat refresher courses on neonatal resuscitation skill decay: an experimental comparative study of in-person and video-based simulation training

Abstract: Neonatal deaths are a major contributor to global under-5-year-old mortality. Training birth attendants can improve perinatal outcomes, but skills may fade over time. In this pilot study, we assessed skill decay of nursing students after remote video versus in-person resuscitation training in a low-resource setting. Filipino nursing students (n = 49) underwent traditional, in-person simulation-based Helping Babies Breathe (HBB) training in Mindanao, Philippines. Participants were then assigned to receive refre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…In a study performed in Guatemala City, in person facilitators were guided by a US‐based master trainer via video conferencing to successfully provide HBB training 6 . Another study in the Philippines found that the Facebook messenger video‐based platform provided sufficient oversight to assess skill acquisition of participants during follow‐up refresher trainings 7 . Such studies were similarly virtually mentored.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a study performed in Guatemala City, in person facilitators were guided by a US‐based master trainer via video conferencing to successfully provide HBB training 6 . Another study in the Philippines found that the Facebook messenger video‐based platform provided sufficient oversight to assess skill acquisition of participants during follow‐up refresher trainings 7 . Such studies were similarly virtually mentored.…”
Section: Discussionmentioning
confidence: 99%
“…This study assessed the viability of a virtually mentored dissemination of this training. While similar studies have taken place in the United States, Guatemala and the Philippines, to the best of our knowledge virtually mentored HBB training has not yet been studied in Africa 5–7 …”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…The original article [ 1 ] contained a typo in author, Nicole A. Shilkofski's name which has since been amended.…”
mentioning
confidence: 99%